Intersection of class, caste, gender and unmet healthcare needs in India: Implications for health policy - Sandhya R. Mahapatro; K.S. James; Udaya S. Mishra (Elsevier, 2021)
Despite renewed policy priorities to universalise health coverage, unmet need for healthcare is long-standing concern in India. The recent data suggests the unmet healthcare need amounts to a notable share of twelve per cent. While studies have examined inequalities in healthcare utilisation in single axes of social power, there was no consensus on the role of the intersectionality between class, caste and gender in shaping the unmet health need. Utilising data from National Sample survey 75th round (2017-18), this paper identifies the factors contributing to such unmet need and investigate the intersectionality of class with caste and gender in determining unmet need. The contribution of socioeconomic factors was assessed by the decomposition method & multivariate logistic regression was used to measure inter and intra-class differentials in unmet need.The analysis informs that class inequality is fundamental to having unmet need with limited role of gender and caste. Economic class however, interacting with caste and gender unfolds wider gaps in access to healthcare. While inter-class differences in unmet need are observed across caste as well as gender, intra-class differences intensify more by caste inequalities. The findings indicate the significance of the intersectional approach in identifying the sources of health inequity and special recognition to the income-poor and socially marginalised in policy agenda. Eliminating the barriers to health care access therefore needs a multidimensional construct of identifying combination of attributes to be focused towards realization of universal health coverage. These observations should aid in formulation and restructuring of the existing healthcare interventions to achieve equity in healthcare provision.